Comparison of complications in isolated aesthetic liposuction procedures across different techniques: a systematic review and meta-analysis - Mohamed Badie Ahmed (10223510) (2025)
Background Liposuction has emerged as one of the most common cosmetic procedures globally, increasing by more than two-fold since 1997. While different liposuction techniques exist, each with distinct advantages and potential sequelae, a comprehensive comparative analysis of complication rates across various techniques in purely aesthetic cases remains unexplored. We aimed to (1) systematically review the literature on complications of distinctliposuction techniques, and (2) compare complication rates between different techniques. Methods PubMed, EMBASE, and Web of Science databases were searched for studies reporting on complications of isolated cosmetic liposuction techniques in specific anatomical regions. Complication rates were pooled, and heterogeneity was assessed using the I² statistic. Publication bias was evaluated using the Luis Furuya-Kanamori index and Doi plot. Results Twenty-three studies were included. Laser-assisted liposuction (LAL) demonstrated the lowest overall complication rates for hemorrhage, infection, seroma formation, thermal injury, and cutaneous necrosis (all 0.13%). Power-assisted liposuction (PAL) exhibited the highest rates for hemorrhage (0.72%), infection (1.34%), and cutaneous necrosis (0.72%). Radiofrequency-assisted liposuction (RFAL) showed the highest rates for seroma formation (3.93%) and thermal injuries/blistering (1.64%). Suction-assisted liposuction (SAL) presented the highest rate of cutaneous irregularities (3.36%). Heterogeneity varied widely across complication types and techniques, with I² values ranging from 0 to 91.4%. Conclusions This study provides the first comprehensive comparison of complication rates across different liposuction techniques in aesthetic cases. LAL demonstrated superior safety profiles, while PAL and RAL showed higher rates for specific complications. These findings can inform surgical decision-making and patient counseling. Level of Evidence Not gradable. Other Information Published in: European Journal of Plastic Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00238-024-02268-0